Gamification for Tourist Guide Application - Elinne Yong; Aslina Baharum; Siti Hasnah Tanalol; Dinna @ Nina Mohd. Nizam; Farhana Diana Deris; Noorsidi Aizuddin Mat Noor (UMS Colloquium on Fundamental Research and Application 2020, 2021)
Tourist Guide application is a mobile application that will be useful for all visitors for a holiday. This application (app) is proposed to provide visitor information about attractive places. Through the app, visitors easily find out the most attractive places by using the map as the app will recommend visitors the top destination to visit. Thus, it is important as they do not have to waste their time seeking information about the location's place and details. The less attractive of the current system affects the user engagement. Thus, the gamification elements that will be implemented in the app can provide a new way of interaction and engagement in a fun and rewarding way. The elements of gamification that will be implemented are point, reward and challenge. The challenge or mini-game, such as quizzes, will make visitors go to the location to find the answers. Not only that, but the visitors also may receive some reward based on the point they collect for each of the correct answers they give. Hence, the app was developed to provide information about the attractions to users and encourage and motivate the users who visit the places. The methodology used for developing the Tourist Guide app is prototyping. The software will be developed in a few phases, including an initial requirement, design, prototyping, customer evaluation, review and update, and final system development.